Autologous Serum Skin Test for Initial Identification of Auto- Antibodies in Chronic Urticaria - Alam, Mohammad Nura; Ali, Mohammad; Khan, Mohammad Moniruzzaman; Tarafder, Keya; Acherjya, Goutam Kumar; Mohith, Muhammad Tanvir (Journal of Medicine, 2018)
Background: Autologous serum skin test (ASST) is easy to perform, cost effective measure for initial identification of auto-antibody in patients suffering from chronic urticaria which may occur due to autoimmune trigger by spontaneously developed auto-antibodies against FcμRI receptor of skin mast cells. Objective: This review is designed to see the positivity of ASST in patients suffering from chronic urticaria. Materials & Methods: This a retrospective data analysis conducted from the records of patients suffered from at least two episodes of urticaria or more in a week for 6 weeks and who did ASST aged more than 10 years between July 2015 to June 2017. These subjects were not pregnant or lactating mother, did not had urticarial vasculitis, predominant co-existing physical urticaria and had negative Hepatitis B antigen and anti-nuclear antibody reports. Results: Total 53 were included in this study of them 33 were female. Mean age was 32 years with a standard deviation (SD) of 11 years. Among study patients 16 (30.2% of total) had a positive ASST result. No age or sex difference was observed in positive ASST cases. In positive cases significant (p-value:<0.001) mean induration difference of 2.75mm with a SD of 1.00 mm observed than induration produced by negative control. Conclusion: ASST is easy and effective tool for initial identification of auto-reactive urticaria. J MEDICINE JUL 2018; 19 (2) : 100-103